Preliminary Results of Relationship between Oil Palm Harvest Losses and Harvest Interval in Riau and West Kalimantan, Indonesia - Nurfalah, Lisa; Dwiyahreni, Asri A.; Winarni, Nurul L.; Mizuno, Kosuke; Grassini, Patricio (Postgraduate, University of Mataram, 2023)
Oil palm smallholders, in particular non-plasma independent smallholders, experience significant yield gaps. Closing this yield gap is important to enhance sustainable livelihoods for oil palm smallholders and reduce the risk of yield increase through expansion. One of the key factors influencing yield is the harvest interval (number of days between two harvesting rounds). Although standards for Good Agricultural Practices regarding oil palm prescribe a harvest interval of 7-10 days, independent smallholders often maintain a harvest interval of 12-30 days. A longer harvesting interval not only reduces the number of fresh fruit bunch harvested per hectare per month but also leads to a larger harvest loss from overripe fruits falling to the ground, deteriorating quickly (harvest loss). We followed an interdisciplinary research approach, combining insights from agronomy and anthropology, to better understand farmers’ practices, and drivers and challenges underlying decision-making. The approach consisted of field audits, farmer surveys, and qualitative interviews to explore which factors impact harvest interval. The harvest interval of smallholders in Riau and West Kalimantan ranged from 11 to 30 days. Farmers followed long harvest intervals (>16-d) due to the low fresh fruit bunch yield. However, longer harvest intervals increased potential harvest losses.